RA09.06: LONG-TERM OUTCOMES OF 650 ESOPHAGEAL CANCER PATIENTS WITH THORACOSCOPIC ESOPHAGECTOMY. (14th September 2018) - Heishi, Takahiro; Ishida, Hirotaka; Onodera, Yu; Ito, Ken; Konno, Takuro; Maruyama, Shota; Sato, Chiaki; Okamoto, Hiroshi; Sakurai, Tadashi; Taniyama, Yusuke; Kamei, Takashi
Abstract: Background: In 1996 Akaishi et al. reported the first thoracoscopic esophagectomy (TE) in Japan. Total 650 TEs for esophageal cancer have been performed in our institute by October 2016. There are many reports about the short-term outcomes of TE compared with open esophagectomy (OE), but the long-term outcomes of TE have been under debate. The aim of this study is to investigate the survival benefits of TE and to compare with OE and long-term outcomes which other previous reports showed. Methods: A total 750 cases who underwent TE (N = 650) or OE (N = 100) between 1994 and 2015 in our hospital were included in this study. They were divided into four groups; surgery without any preoperative treatments (group S, N = 414), surgery after neoadjuvant chemotherapy (Group NAC, clinical stage II or III, N = 116), surgery after neoadjuvant chemoradiotherapy (Group NACRT, clinical stage II or III, N = 68) and salvage surgery after definitive chemoradiotherapy (Group SALV, N = 76). In group S, 100 patients received OE and 314 received TE. The other 3 groups (Group NAC, NACRT and SALV) received only TE. 3-year, 5-year overall survival (OS) and progression-free survival (PFS) rates for each group were analyzed and compared. Results: In group S, the 5-year OS rate of TE was 63.4% and that of OE was 68.3%, there was no significant difference (Log-Rank test P  = 0.41). Stage-specific OS rates of TE and OE were also compared and there was no significant difference. PFS rates of OE and TE showed the same tendency of OS. 5-year OS rate of group NAC was 63.5%. 3-year OS of group NACRT was 61.4%. 3-year and 5-year OS of group SALV were 41.4% and 34.0%. These results were the same or better than what the previous reports showed. Conclusion: The long-term outcomes of TE were almost same as those of OE. The TE procedure resulted in similar or potentially better long-term outcomes in case of NAC, NACRT and SALV. It's acceptable to say thoracoscopic approach is the standard of esophagectomy. Disclosure: All authors have declared no conflicts of interest.